2007
DOI: 10.1179/146531207225021852
|View full text |Cite
|
Sign up to set email alerts
|

Breakages using a unilateral fixed functional appliance: a case report using The ForsusTMFatigue Resistant Device

Abstract: Fixed functional appliances are designed to provide a simple non-compliant solution to orthodontic Class II treatment. Molar correction can be achieved very quickly using these appliances, but the clinician should be wary of unexpected breakages. This case report documents such an occurrence using a unilateral fixed functional appliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 5 publications
1
9
1
2
Order By: Relevance
“…The breakage rate, which resulted in extra visits reported in this study, was seemingly much greater than that which was reported by Ross et al 8 Seventeen FFRD springs had been placed. Although they noted 10 incidents, eight incidents were lost split crimps.…”
contrasting
confidence: 52%
See 1 more Smart Citation
“…The breakage rate, which resulted in extra visits reported in this study, was seemingly much greater than that which was reported by Ross et al 8 Seventeen FFRD springs had been placed. Although they noted 10 incidents, eight incidents were lost split crimps.…”
contrasting
confidence: 52%
“…Durability of an appliance is another important consideration when evaluating an orthodontic device and certainly plays a major role in a patient's experience. No quantification of FFRD failures could be found in the literature, except a case report 8 indicating two breakage incidents.…”
Section: Introductionmentioning
confidence: 97%
“…The device allows patient to open and move their jaw more freely. 7,8 The Forsus Nitinol Flat Spring (FNFS) is an alternative fixed functional appliance described by Vogt in 2001. 9 It has a Nitinol flat wire instead of the coil which is more esthetically acceptable.…”
Section: Forsus: Fatigue Resistant Devicementioning
confidence: 99%
“…Unitek, force levels are similar to Class II elastics, as are the treatment effects, except that Class II correction is typically seen quicker as the Forsus is fixed and cooperation is not an issue as it is with Class II elastics. 115 There have been case reports of the fatigue resistant module breakage 116 however, other studies document the good resiliency of the Niti springs. 117 An updated EZ module has also been released to help reduce breakage, and recent 3M Unitek literature states that the Forsus appliance has been compression cycled tested over 5 million times without breakage or force fatigue.…”
Section: The Forsus Frdmentioning
confidence: 99%